Analysis of the Utilization of Village Funds in the Field of Community Empowerment to Improve the Welfare of the Adabang Village Community - Anselma Vitusia Ajeng Wada; Konstantinus Pati Sanga; Petrus Da Silva; Thadeus Fransesco Quelmo Patty (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the use of village funds in the field of community empowerment to improve community welfare in Adabang Village, Titehena District, East Flores Regency. The research adopts a qualitative descriptive method involving observation, interviews, and documentation. Informants include the Village Head, village officials, BPD members, and the community. Findings indicate that the use of village funds has focused on empowerment activities such as agricultural support, food security, and the development of early childhood education centers. The study also highlights issues such as limited community participation, weak administrative capacity, and lack of sustainability awareness. Nevertheless, the programs have contributed to improving social and economic welfare, reflecting public financial management principles of transparency, accountability, and participation.